Origin, evolution and dynamic context of a Neoglacial lateral-frontal moraine at Austre Lovénbreen, Svalbard - Midgley, Nicholas G.; Cook, Simon J.; Graham, David J.; Tonkin, Toby N. (Geomorphology, 2013)
Moraines marking the Neoglacial limits in Svalbard are commonly ice cored. Investigating the nature of this relict ice is important because it can aid our understanding of former glacier dynamics. This paper examines the composition of the lateral-frontal moraine associated with the Neoglacial limit at Austre Lovénbreen and assesses the likely geomorphological evolution. The moraine was investigated using ground-penetrating radar (GPR), with context being provided by structural mapping of the glacier based on an oblique aerial image from 1936 and vertical aerial imagery from 2003. Multiple up-glacier dipping reflectors and syncline structures are found in the GPR surveys. The reflectors are most clearly defined in lateral positions, where the moraine is substantially composed of ice. The frontal area of the moraine is dominantly composed of debris. The core of the lateral part of the moraine is likely to consist of stacked sequences of basal ice that have been deformed by strong longitudinal compression. The long term preservation potential of the ice-dominated lateral moraine is negligible, whereas the preservation of the debris-dominated frontal moraine is high. A glacier surface bulge, identified on the 1936 aerial imagery, provides evidence that Austre Lovénbreen has previously displayed surge activity, although it is highly unlikely to do so in the near future in its current state. This research shows the value of relict buried ice that is preserved in landforms to aiding our understanding of former glacier characteristics.